Barriers and facilitators to implementing core osteoarthritis treatments in China: a mixed-method study - Guoxin Ni; Ziru Wang; Shuning Duan; Xier Chen; Huili Deng; Yunqi Wang (BMJ Open)
Objective To understand current practices and identify barriers and facilitators to implementing guideline-recommended core osteoarthritis (OA) treatments in China.Design An exploratory mixed-methods designSetting Public and private clinical institutions across mainland China.Participants A total of 498 healthcare professionals participated. The qualitative phase included semistructured interviews (n=15) and a qualitative survey (n=181). The quantitative phase consisted of a survey with 302 respondents across 19 provinces, representing seven health professions.Results Five themes identified as barriers during the qualitative phase: misconceptions about OA; limitations in current medical insurance policies; insufficient multidisciplinary collaboration; lack of workplace support and low patient adherence to self-management. Three themes identified as facilitators: telehealth and community-based delivery pathways; professional training and patient education resources; and personalised services with positive feedback. Quantitative findings showed that physical agent therapy (56%) and traditional Chinese medicine (22%) were the most frequently used OA treatments, while exercise therapy was implemented in only 9% of cases. The average OA knowledge score was 31.2 (±8.9) out of 55, with the lowest self-rated confidence in interdisciplinary collaboration (3.4±0.1, ‘somewhat confident’). The most applicable factors impacting the implementation of core OA treatments included patient comorbidities, knowledge of pain science and exercise therapy, and financial support (all 2.8±0.8, ‘applicable’).Conclusions The uptake of core OA treatments in China remains suboptimal, constrained by limitations in insurance coverage, workforce capacity and interdisciplinary integration. Enhancing telehealth accessibility, strengthening professional training and refining policy incentives may help bridge this evidence-practice gap and improve OA management in China.